Hypoglycemic and hypolipidemic activities of Arabic and Indian origin Salvadora persica root extract on diabetic rats with histopathology of their pancreas - Khan, Maria; Ali, Mohammad; Ali, Abuzer; Mir, S.R. (International Journal of Health Sciences, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--> Objective: To evaluate hypoglycemic and hypolipidemic effects of Salvadora persica aqueous extracts on streptozotocin-induced diabetic rats by measuring fasting blood glucose levels, lipid profiles and histopathological analysis of pancreas. Materials and Methods: Experimental Diabetes was induced by single intraperitoneal injection of streptozotocin (60 mg/kg) to albino Wistar rats. Salvadora persica extracts were administered orally at 250 and 500 mg/kg dose levels for 21 days. Glucose tolerance test (GTT) was performed on 16 h fasted rats and changes in blood glucose levels, total cholesterol, triglycerides, low-density lipoprotein (LDL), very low density lipoprotein (VLDL), high density lipoprotein (HDL) and histopathology of pancreas were performed. Results:At a dose level of 500 mg/kg, blood glucose 85.25 ± 13.20 mg/dl, total cholesterol (TC) 114.57 ± 15.81(mg/dl), triglycerides (TG) 75.40 ± 16.47(mg/dl), LDL 42.63 ± 13.17(mg/dl), VLDL 22.78 ± 1.88(mg/dl), and elevation of HDL 44.88 ± 11.61(mg/dl) were found in comparison with diabetic control on 28th day by Arabic origin Salvadora persica. It also accelerated the regeneration of β-cells in experimental animal’s pancreas to 32.6 ± 2.4 compared to diabetic control animal’s pancreas of 8.1 ± 0.5 at the end of 28th day. Conclusion: This study confirmed that Arabic Salvadora persica aqueous extracts at 500 mg/kg dose level, in comparison to other extracts (Indian Salvadora persica, 250 and 500 mg/kg, Arabic Salvadora persica 250 mg/kg) possessed significant hypoglycemic and hypolipidemic activities and regenerated pancreatic β-cells in streptozotocin treated diabetic rats. Key words: Salvadora persica, geo-comparison, antidiabetic activity, hypoglycemic activity, serum lipid profile, glucose tolerance test, histopathology, pancreatic β-cells, <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->